2016
DOI: 10.1007/s11581-016-1713-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrobenzene electrochemical sensor based on silver nanoparticle supported on poly-melamine functional multi-walled carbon nanotube

Abstract: A novel and convenient electrochemical sensor, based on multi-walled carbon nanotube (MWCNT)-polymelamine(PMel)-silver nanoparticle (AgNP) compositemodified glassy carbon electrode (GCE), was fabricated for the determination of nitrobenzene (NB). The modified electrode not only played an efficient electrocatalytic role for the reduction of NB but also significantly reduced the overpotential of NB, and the peak current increased greatly compared with bare GCE or other modified electrodes. The excellent performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The broad P1 peak in the potential range of −0.3 V and 0.2 V and P2 peak in the range of −0.6 V and −0.3 V were associated to electrochemical oxidation of glucose into gluconolactone, while the N1 peak in the potential range of −0.65 and −0.25 V originated from further oxidation or removal of the intermediates and the reduction of Pd oxides. In contrast, nanostructured Ag is inactive for electrochemical glucose detection . We further summarized the mass activities of bimetallic PdAg NWs with different compositional ratios based on the peak intensities of P1 (Figure d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad P1 peak in the potential range of −0.3 V and 0.2 V and P2 peak in the range of −0.6 V and −0.3 V were associated to electrochemical oxidation of glucose into gluconolactone, while the N1 peak in the potential range of −0.65 and −0.25 V originated from further oxidation or removal of the intermediates and the reduction of Pd oxides. In contrast, nanostructured Ag is inactive for electrochemical glucose detection . We further summarized the mass activities of bimetallic PdAg NWs with different compositional ratios based on the peak intensities of P1 (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, nanostructured Ag is inactive for electrochemical glucose detection. [36,37] We further summarized the mass activities of bimetallic PdAg NWs with different compositional ratios based on the peak intensities of P1 (Figure 3d). Obviously, ultrathin Pd 2 Ag 1 singlecrystalline NWs displayed the best performance toward electrochemical detection of glucose.…”
Section: Resultsmentioning
confidence: 99%
“…Ren et al devised a sensitive electrochemical sensor to detect nitrobenzene on immobilized silver NPs (AgNP)-PME- MWCNT on a GCE . It has been found that the modified electrode had an effective electrocatalytic contribution to reduce NBz and remarkably declined the nitrobenzene overpotential; therefore, the peak current enhanced greatly compared with the bare GCE or the other modified electrodes.…”
Section: Polymer Nanocomposites-based Electrochemical Sensors For The...mentioning
confidence: 99%